Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T20:03:27+01:00
X=1+4√3 i y=4-2√3

1)
x+y=1+4√3+4-2√3=5+2√3
2)
x-y=1+4√3-4+2√3=-3+2√3
3)
xy=(1+4√3)(4-2√3)=4-2√3+16√3-24=-20+14√3
4)x/y=(1+4√3)/(4-2√3)=1+4√3)(4+2√3)/16-12=4+2√3+16√3-24/4=28+18√3/4=2(14+9√3)/4=14+9√3/2
5)
x²=(1+4√3)²=1+8√3+48=49+8√3
6)
2x-3y=2(1+4√3)+3(4-2√3)=2+8√3+12-6√3=14+2√3=2(7+√3)
2010-03-17T20:11:13+01:00
X=1+4√3 i y=4-2√3
a) obliczam x+y
1+4√3+4-2√3=5+2√3
b)obliczam x-y
1+4√3-(4-2√3)=1+4√3-4+2√3=-3+6√3=3(-1+2√3)
c) obliczam xy
(1+4√3)(4-2√3)=4-2√3+16√3-8*3=4-14√3-24=-20-14√3=2(10-7√3)
d)obliczam x/y
1+4√3 4+2√3 4+2√3+16√3+8*3 28 +18√3
------- * --------- = ----------------------- = ------------- = 7+4,5√3
4-2√3 4+2√3 16-4*3 4

d)x²
(1+4√3 )²=1+8√3 +16*3=1+8√3 +48=49+8√3
e)2x-3y
2(1+4√3)-3(4-2√3)=2+8√3-12+6√3=-10+14√3=2(-5+7√3)
2010-03-17T21:03:30+01:00
Dane sa liczby: x=1+4√3 i y=4-2√3 oblicz:
x+y ,
1+4√3+4-2√3=5+2√3
x-y ,
1+4√3-4+2√3=6√3-3
xy ,
(1+4√3)(4-2√3)=4-2√3+16√3-24=14√3-20
x/y ,
(1+4√3):(4-2√3)=(1+4√3)(4+2√3):(4-2√)(4+2√3)=(4+2√3+16√3+24):(16-12)=(18√3+28):4=(9√3+14):2
x² ,
(1+4√3)²=1+2*4√3+16*3=1+8√3+48=8√3+49
2x-3y =2(1+4√3)-3(4-2√3)=2+8√3-12+6√3=14√3-10=2(7√3-5)